Crustal thermal structure and thermal anomaly mechanism in the southern part of the Jizhong Depression, China - Wang, Lijun; Xing, Linxiao; Lin, Wenjing; Liu, Lu (Frontiers in Earth Science, 2025)
IntroductionThe lithospheric thermal structure, which reflects the thermal evolution of the lithosphere, serves as a critical scientific basis for the development of deep geothermal resources.MethodsUsing geothermal well logging and the tests of rock thermophysical properties in the Gaoyang geothermal field, this study preliminarily determined the characteristics of the terrestrial heat flow and lithospheric thermal structure in the southern Jizhong Depression. Furthermore, this study established a conceptual model for the lithospheric thermal structure in the study area and estimated the deep geothermal distribution in the area.ResultsThe results indicate that the Gaoyang geothermal field exhibits a terrestrial heat flow value of 67.19 mW/m2, Moho temperatures ranging from 697.16 °C to 774.54 °C, Curie point depths varying from 22.38 km to 24.09 km, and thermal lithosphere thicknesses ranging from 58.14 km to 75.16 km. The results of this study are largely consistent with previous findings, verifying the accuracy of the established model. Regional deep-seated faults penetrate the lithosphere, creating favorable conditions for deep mantle-derived materials and magmas to intrude into the crust.DiscussionConsequently, heat flow from sags with low thermal conductivity converges into uplifts with high thermal conductivity. Deep groundwater circulation along these faults enhances heat convection, resulting in heat accumulation within fractured carbonate rocks. Furthermore, the overlying sandy mudstones with low thermal conductivity act as cap rocks with effective thermal insulation. The combined effects of these favorable factors contribute to the formation of high-temperature geothermal reservoirs in the southern Jizhong Depression.